Stratigraphy of the Neogene Sahabi units in the Sirt Basin, northeast Libya. (June 2016) - El-Shawaihdi, M.H.; Mozley, P.S.; Boaz, N.T.; Salloum, F.; Pavlakis, P.; Muftah, A.; Triantaphyllou, M.
Abstract: A revision of the nomenclature of lithostratigraphic units of Neogene strata at As Sahabi, northeast Libya, is presented, based on new fieldwork conducted during 2006–2008. The Sahabi units are correlated across the Ajdabya Sheet (NH 34-6) in northeastern Libya. Major conclusions are: (1) Miocene (Langhian through Messinian) strata are predominantly carbonate and should be referred to as formation "M"; (2) A local unconformity of Miocene (early Messinian) age overlies strata of the formation "M"; (3) This unconformity is overlain by Messinian gypsiferous sand and mud (formerly formation "P" and partially member "T"), which are designated as the "lower member" (gypsiferous) of the Sahabi Formation; (4) The "lower member" is overlain by sand and mud of late Messinian age (formerly partially member "T" and members "U1", "UD", and "U2") in a generally fining-upwards sequence, and are designated as the "upper member" (non-gypsiferous) of the Sahabi Formation; (5) The latest Miocene sand and mud of the "upper member" are capped by an unconformity that is correlated with the regression and desiccation of the Mediterranean Sea during the Messinian Salinity Crisis and with Eosahabi Channel cutting; (6) The unconformity is overlain by Pliocene medium, coarse, and pebbly sands, which are referred to as the Qarat Weddah Formation (formerly Garet Uedda Formation); (7) The Pliocene sands of Qarat Weddah Formation are overlain by carbonate soil (calcrete) of Late Pliocene age, which is referred to as formation "Z" (formerly member "Z"). The major outcome of this study is a revised stratigraphic description and nomenclature of the Sahabi units that helps to provide a formal and unified context for understanding paleontological discoveries in northeastern Libya, which will serve to facilitate a broader correlation of the Sahabi units with their equivalents elsewhere in Africa and in Europe and Asia. Highlights: Our results help eliminate major discrepancies among lithostratigraphic nomenclature of Neogene units in northeastern Libya. The study provides, for the first time, a lithostratigraphic correlation of rock units in northeastern Libya. Previous informal lithostratigraphic has been replaced.